IMPLEMENTATION OF INDONESIAN PUBLIC DIPLOMACY IN SAUDI ARABIA THROUGH THE 2018 JANADRIYAH FESTIVAL: Implementasi Diplomasi Publik Indonesia di Arab Saudi Melalui Festival Janadriyah 2018 - Rozikin; Ratu Priyanto; Helga Simatupang (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Indonesia's bilateral relations with Saudi Arabia have strategic value in the political, economic, social, and religious fields in the Middle East and Southeast Asia. Within this framework, public diplomacy is an important instrument of foreign policy for shaping international public perception and building a positive image of the country. This study aims to examine the implementation of Indonesia's public diplomacy in Saudi Arabia through its participation in the 2018 Janadriyah Festival using Nicholas J. Cull's theory of public diplomacy. This study uses a descriptive qualitative approach with secondary data obtained through literature studies from books, theses, dissertations, journals, scientific articles, and credible online sources. The results of the study show that Indonesia's participation in the 2018 Janadriyah Festival was driven by shared values with Saudi Arabia, particularly in the aspects of religion and education. Government support was also a major factor because this activity was in line with Indonesia's foreign policy direction. The festival played a role in introducing and preserving Indonesian culture in Saudi Arabia. Based on Cull's analysis, Indonesia's public diplomacy is reflected through five elements, namely listening, advocacy, cultural diplomacy, exchange diplomacy, and international broadcasting, which are manifested through the formation of public opinion, institutional cooperation, cultural strengthening, community interaction, and media collaboration.